Comprehensive model for energetic analyses of a series hybrid-electric vehicle powered by a passive Turbulent Jet Ignition engine. (1st October 2022) - Frasci, Emmanuele; Cervone, Davide; Nacci, Gianluca; Sementa, Paolo; Arsie, Ivan; Jannelli, Elio; Maria Vaglieco, Bianca
Highlights: 1-D engine model with predictive TJI combustion is developed and exp. validated. TJI engine operation is exploited by 1-D model. A comprehensive model of series-HEV is designed by 1-D simulation results. The benefits of TJI concept on overall efficiency and battery sizing are assessed. Abstract: In the last decades, the concern about vehicles' environmental impact has progressively increased. Therefore, car manufacturers are moving towards vehicles with low emissions like Hybrid Electric Vehicles (HEV), that in the series architecture utilize an internal combustion engine (ICE) to power an electric generator for battery recharging thus extending the driving range of a Battery Electric Vehicle (BEV). For such applications, small four-stroke spark-ignition (SI) engines are a suitable solution, as they are proven low-cost and reliable systems and allow to increase vehicle driving range with reduced environmental impact. In series HEV the ICE is decoupled from the drive wheels and operates at a fixed working point regardless to the instantaneous power demand, thus promoting the lean mixture operation to achieve high efficiency and low CO2 emissions. In this work, the performance, in terms of driving range, energy consumption and CO2 emissions, of a series HEV are analyzed in experimental and simulation environment. Particularly, the Auxiliary Power Unit (APU) is a small ICE equipped with a passive Turbulent Jet Ignition (TJI) that allows to guarantee stable combustion also under lean mixture operation, with an increase of engine efficiency and a reduction of CO2 emissions. The effects of lean air–fuel ratio on combustion process and engine performance are investigated by a one-dimension (1-D) model and validated vs experimental measurements at the test bench on a prototype single cylinder engine equipped with passive prechamber. The benefits of the high efficiency ICE operation on the series HEV performance, energy consumption and CO2 emissions vs standard and arbitrary driving cycles are analyzed in simulation environment, making use of the simulation results gathered by the 1-D engine model. Simulation analyses are carried out to evaluate the best compromise between battery pack downsizing and energy consumption for a fixed target of vehicle drive range. Simulation results show that TJI concept allows to achieve an APU efficiency up to 32 %, by operating with λ equal to 1.26. Additionally, the analysis on battery pack downsizing evidences that switching from 150 % to 50 % of the reference battery pack capacity results in an increase of the overall energy consumption up to 22 %.